Design and development of a 2-DoF tilt-rotor quadcopter - Ang, Zheng Da (Nanyang Technological University, 2020)
This report presents the design and development of a quadcopter with fully actuated propellers through the implementation of 2-DoF tilt-rotor mechanisms. A quadcopter with fully actuated propellers is more agile and manoeuvrable, as the propellers can be rotated in their elevation and bank axes using tilt-rotor mechanisms to confer thrust vectoring capabilities. Also, the fault tolerance characteristics of a quadcopter can be enhanced with fully actuated propellers. This prevents a catastrophic loss of control that could otherwise happen in conventional quadcopters with coplanar propellers, should there be any motor or propeller failure. In this report, an optimised design for the quadcopter platform is proposed, detailing the optimisation process and the structural considerations of the fully actuated propellers. Static and dynamic analyses of the designed quadcopter structure are also performed to investigate the potential stress and vibrational effects. With the advent of 3D printing and its game-changing role in the manufacturing industry, the 3D printing processes of the designed quadcopter components are explored to provide an insight into effective manufacturing. Thereafter, this report documents the experimental testing of the tilt-rotor actuation mechanism. The processed experimental results are used to ascertain optimal servo parameters, quantify induced forces and moments, and characterise motor-propeller attributes. An electronic system schematic to power and control the servos and motors concurrently is also proposed. Finally, this report provides the physical attributes of the assembled quadcopter for the purpose of mathematical modelling.